Testing the Existence of Environmental Kuznets Curve (EKC) Hypothesis in ASEAN 5 - Pratama, Adhy Satya; Pudjihardjo, M.; Manzilati, Asfi; Pratomo, Devanto Shasta (Technium Social Sciences Journal, 2021)
This study aims to test the existence of the Environmental Kuznets Curve (EKC) hypothesis in cases of economic growth and environmental degradation caused by carbon dioxide (CO2) emissions in 5 ASEAN countries (Indonesia, Malaysia, Thailand, the Philippines and Singapore). To see the existence of the EKC hypothesis in each country in ASEAN 5, it is done by combining the economic growth and CO2 emission data graphs to see the EKC turning point. The results of the analysis show that the turning points are different in each country. Indonesia is a country with the largest amount of CO2 emissions with an EKC pattern, namely M-shape. Thailand has the same EKC pattern as Indonesia but with slightly lower CO2 emissions due to a lower economic growth rate. Malaysia, Philippines and Singapore have EKC patterns with more turning points. Singapore has the lowest CO2 emissions with the highest economic growth rate.